Variants of SLC39A4 cause acrodermatitis enteropathica in Tibetan, Yi, and Han families in Sichuan region of southwestern China: a case report series - Li, Zhongtao; Wang, Sheng (Frontiers in Medicine, 2024)
Acrodermatitis enteropathica (AE, OMIM 201100) is a rare autosomal recessive dermatosis characterized by periorificial dermatitis, diarrhea, alopecia, and hypozincaemia due to pathogenic variants of SLC39A4. Herein, we present a case series describing four unrelated patients with AE from Han, Yi, and Tibetan ethnicities in Sichuan region of southwestern China, speculate the hotspot variants of SLC39A4 causing AE in Sichuan region and highlight physicians should be alerted to unusual presentations of AE, such as the absence of hypozincaemia and the presence of acne-like lesions. Serum alkaline phosphatase and genetic testing should be considered to accurately evaluate the zinc deficiency in human body and help make the correct diagnosis.